Evaluating sports complex sustainable supply chains: A prospective assessment technique method of moments quantile regression research - Jialong Liu; Xin Su; Yang Wang (PLoS ONE, 2025)
The growing emphasis on sustainability in supply chain management has raised critical concerns about its implementation in complex ecosystems such as sports stadiums. This study investigates the economic and environmental dimensions of sustainable supply chains within sports complexes, employing the Method of Moments Quantile Regression (MMQR) technique to provide a nuanced analysis of key variables influencing sustainability outcomes from 2008 to 2022. By integrating Corporate Environmentalism (CE), Population Density (PD), Economic Complexity Ratio, and Workforce Readiness Ratio with Gross Domestic Product (GDP) differentiation metrics, the research identifies significant conditional and non-linear relationships. Results reveal that CE plays a pivotal role in driving GDP differentiation, particularly in lower quantiles, highlighting the potential of sustainability to contribute to balanced economic growth. Population Density consistently influences sustainability outcomes, underscoring the critical role of demographic factors. Additionally, the study exhibit strong macroeconomic and social implications, emphasizing the importance of inclusive strategies for sustainable development. Notably, higher GDP differentiation quantiles reveal trade-offs between economic and environmental goals, presenting challenges for achieving equilibrium. These findings suggest that policymakers and stakeholders should adopt tailored strategies to balance economic and environmental objectives, fostering sustainable practices in sports stadium ecosystems while mitigating disparities across different economic conditions.